1994
DOI: 10.1161/01.cir.89.1.122
|View full text |Cite
|
Sign up to set email alerts
|

Intramural myocardial shortening in hypertensive left ventricular hypertrophy with normal pump function.

Abstract: BACKGROUND In hypertensive left ventricular hypertrophy (LVH), intrinsic myocardial systolic function may be normal or depressed. Magnetic resonance tagging can depict intramural myocardial shortening in vivo. METHODS AND RESULTS Tagged left ventricular magnetic resonance images were obtained in 30 hypertensive subjects with LVH (mean LV mass index, 142 +/- 41 g/m) and normal ejection fraction (mean, 64 +/- 9%) using spatial modulation of magnetization.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
91
1
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(108 citation statements)
references
References 57 publications
13
91
1
3
Order By: Relevance
“…Thus a pseudo-normal LV chamber systolic function in the presence of concentric geometry is an expression of depressed myocardial function, suggesting that endocardial shortening is a poor index of real LV function. Furthermore, our ultrasonic data (MFS and CVI) were consistent with the MRI study, 20,21 which showed that intramural myocardial shortening is depressed in hypertensives with LVH and with a 'pseudonormal' left ventricular function. In fact in our study no linear relationship was found between CVI and left ventricular fractional shortening, but we have demonstrated a significant correlation between a depressed MFS and our videodensitometric index of systo-diastolic change in mean gray level, indicating that this variation of echo amplitude could be considered a distinct, 'early' index of an altered myocardial function.…”
Section: Myocardial Midwall Mechanics and Ultrasonic Textural Parameterssupporting
confidence: 88%
See 2 more Smart Citations
“…Thus a pseudo-normal LV chamber systolic function in the presence of concentric geometry is an expression of depressed myocardial function, suggesting that endocardial shortening is a poor index of real LV function. Furthermore, our ultrasonic data (MFS and CVI) were consistent with the MRI study, 20,21 which showed that intramural myocardial shortening is depressed in hypertensives with LVH and with a 'pseudonormal' left ventricular function. In fact in our study no linear relationship was found between CVI and left ventricular fractional shortening, but we have demonstrated a significant correlation between a depressed MFS and our videodensitometric index of systo-diastolic change in mean gray level, indicating that this variation of echo amplitude could be considered a distinct, 'early' index of an altered myocardial function.…”
Section: Myocardial Midwall Mechanics and Ultrasonic Textural Parameterssupporting
confidence: 88%
“…The relevance of the evaluation of the midwall left ventricular mechanics in the analysis and prognosis of hypertensive patients has been demonstrated in several studies with different methodological approaches (haemodynamic, echo, nuclear magnetic resonance), which take into account the epicardial migration of the midwall during systole. [19][20][21] On the other hand, endocardial fractional shortening overestimates the left ventricular myocardial performance in hypertensive patients and is probably an imperfect index of left ventricular chamber mechanics rather than of myocardial performance. 3 Moreover, in hypertrophic myocardial walls, less intramural percent segment shortening is necessary for the same absolute systolic wall thickening and for the endocardial motion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of myocardial contractile function in the hypertrophied left ventricle resulting from hypertension suggest that intrinsic myocardial performance may be depressed, even when left ventricular ejection fraction remains normal. 82 However, the presumed innocent nature of the athlete's heart does not allow the performance of more invasive studies in athletes. Left ventricular diastolic function is commonly assessed by studying the pattern of ventricular filling through the mitral valve.…”
Section: Cardiac Functionmentioning
confidence: 99%
“…function is reduced in the presence of LV hypertrophy, and midwall function is able to discriminate subjects with and without LV hypertrophy better than traditional chamber function indexes. 1,[9][10][11] However, the strongest correlate of midwall function is LV geometric pattern, concentric geometry (expressed as relative wall thickness) being a powerful determinant of reduced midwall function. 6,12,13 A marked increase in relative wall thickness was recently reported in 42 hypertensive patients with depressed LV midwall function compared with 117 hypertensive subjects with normal midwall function, even in the absence of differences in LV mass between the groups.…”
Section: Introductionmentioning
confidence: 99%